Early hydration properties and microstructure evolutions of MgO-activated slag materials at different curing temperatures. Issue 12 (15th June 2022) - Ma, Hongqiang; Zhang, Shaochen; Feng, Jingjing
Abstract: This study reports on the early hydration properties and microstructure evolutions of MgO-activated slag at five curing temperatures (20 °C, 40 °C, 50 °C, 60 °C, and 80 °C) and three MgO types (S-MgO, M − MgO, and R-MgO). The results indicated that high-temperature curing substantially increased the compressive strength of the specimens. Particularly, the highest strength was obtained at 40 °C and 60 °C for the S-MgO and M-MgO-activated slag specimens, respectively, and the high curing temperature for the R-MgO-activated slag specimen was 40 °C. We focused on the relationship between the mechanical properties, pore structure characteristics, and hydration products. The combination of calcium-silicate-hydrate (C-S-H) gel and Al increased under high-temperature curing conditions. XRD, FT-IR, TG-DTG, and 27 Al MAS-NMR results showed a high Al content in the formation of calcium silicate hydrate with Al in its structure (C-A-S-H gel) for the R-MgO-activated slag pastes under high-temperature curing; however, the microstructure was loose owing to the formation of excessive brucite. For the S-MgO-activated slag specimen, the Ca/Si ratio was high, with more Mg 2+ penetrating the C-S-H gel interlayer, forming more hydrotalcite-like phases and increasing the chain length of the C-S-H gel. The microstructure showed good compatibility of the hydration products interweaving to form dense microstructures.